The Emerald ash borer Agrilus planipennis Fairmaire (Coleoptera: Buprestidae) invaded Belarus - Zviagintsev, Vyacheslav B.; Kirichenko, Natalia I.; Chernik, Maxim I.; Seraya, Lidia G.; Baranchikov, Yuri N. (Acta Biologica Sibirica, 2025)
The emerald ash borer, Agrilus planipennis Fairmaire, 1888 (Coleoptera: Buprestidae), is a harmful East Asian insect pest damaging ash trees Fraxinus spp. Over the past three decades, it has invaded European part of Russia and Ukraine, causing widespread mortality of ash trees in both urban and natural ecosystems. Here, we report first occurrence of this devastating pest in Belarus, specifically in the city of Gomel. During reconnaissance survey performed in the late June 2025, a total of 46 ash trees, including 39 Fraxinus pennsylvanica and 7 F. excelsior trees, displayed characteristic symptoms of infestation: canopy dieback, epicormic sprouting, and distinct D-shaped exit holes in the bark. A single larva of the IV instar was found within a typical gallery beneath the bark, and 13 adult beetles mating and feeding on the foliage of both ash species were recorded. Given the proximity of infested regions in neighboring countries – specifically Bryansk (243 km away from Gomel) and Smolensk (270 km) in Russia, as well as Kiev (220 km) in Ukraine – it is suspected that the buprestid was accidentally introduced from some of these localities rather than expanding its range by itself. Urgent research is required to delineate the extent of its spread within Belarus. Moreover, decisive actions must be taken promptly to suppress current infestation foci and prevent further distribution of this highly aggressive alien pest.